Digital Literacy for Individuals with Intellectual and Developmental Disabilities in Education: A Systematic Literature Review - Ringwood, Barbara (Master of Education, 2024)
This systematic review of the literature research study aims to explore how digital literacy and digital competencies are being defined and utilised within the research for people with intellectual and developmental disabilities. The review focused on both educational and health-based databases for this process. Through a rigorous selection where rules for inclusion and exclusion were defined, a final tally of forty-five articles were selected from an initial set of nine hundred and eighty-eight. Findings show that the term digital literacy is ill defined in the research literature. There is a broad range of other terminology used to define digital literacy, ranging from computer skills to technology skills. Some technological barriers to digital literacy are highlighted within the literature and most of these barriers are external factors, situated outside of the person. Further, many of the barriers to digital literacy and integration that existed twenty years ago persist today. In conclusion many researchers working within intellectual and developmental disability are not defining the term digital literacy within the research literature and this needs to be considered within future research.
PRESENTED
Keywords: SOCIAL SCIENCES::Social sciences::Education; Digital literacy; Digital Competency; Intellectual and Developmental Disability; Systematic Review; Digital Engagement; Computer Education/Literacy; Computers & Education; Disability Inclusion; EDUCATION; Higher Education; INTELLECTUAL DISABILITY; Inclusive Education; Intellectual Disability; Education